Tobin's q and the Importance of Focus in Firm Performance - Wernerfelt, Birger; Montgomery, Cynthia A. (American Economic Review, 1988)
Using Tobin's q as a measure of performance, we seek to estimate the relative importance of industry, focus, and share effects in determining firm performance. Our methods are analogous to those of Richard Schmalensee and, like him, we find that industry effects account for the majority of the explained variance. However, we also find that firm effects exist in the form of focus effects, that is, narrowly diversified firms do better than widely diversified firms. We interpret this finding as consistent with profit maximization by firms with different factor endowments.